The pricing of digital art - Yi-Hsuan Chen; Roman Kräussl; Patrick Verwijmeren (Goethe University Frankfurt, Center for Financial Studies (CFS), 2023)
The intersection of recent advancements in generative artificial intelligence and blockchain technology has propelled digital art into the spotlight. Digital art pricing recognizes that owners derive utility beyond the artwork's inherent value. We incorporate the consumption utility associated with digital art and model the stochastic discount factor and risk premiums. Furthermore, we conduct a calibration analysis to analyze the effects of shifts in the real and digital economy. Higher returns are required in a digital market upswing due to increased exposure to systematic risk and digital art prices are especially responsive to fluctuations in business cycles within digital markets.
Keywords: D8; 330; Digital art; conspicuous consumption; utility dividends; risk premium; valuation